Illuminating the role of the Gα heterotrimeric G protein subunit, RGA1, in regulating photoprotection and photoavoidance in rice. (9th January 2018) - Ferrero‐Serrano, Ángel; Su, Zhao; Assmann, Sarah M.
Abstract: We studied physiological mechanisms of photoavoidance and photoprotection of a dwarf rice mutant with erect leaves, d1, in which the RGA1 gene, which encodes the Gα subunit of the heterotrimeric G protein, is non‐functional. Leaves of d1 exhibit lower leaf temperature and higher photochemical reflectance index relative to wild type (WT), indicative of increased photoavoidance and more efficient light harvesting. RNA sequencing analysis of flag leaves revealed that messenger RNA levels of genes encoding heat shock proteins, enzymes associated with chlorophyll breakdown, and ROS scavengers were down‐regulated in d1 . By contrast, genes encoding proteins associated with light harvesting, Photosystem II, cyclic electron transport, Photosystem I, and chlorophyll biosynthesis were up‐regulated in d1 . Consistent with these observations, when WT and d1 plants were experimentally subjected to the same light intensity, d1 plants exhibited a greater capacity to dissipate excess irradiance (increased nonphotochemical quenching) relative to WT. The increased capacity in d1 for both photoavoidance and photoprotection reduced sustained photoinhibitory damage, as revealed by a higher F v / F m . We therefore propose RGA1 as a regulator of photoavoidance and photoprotection mechanisms in rice and highlight the prospect of exploiting modulation of heterotrimeric G protein signalling to increase these characteristics and improve the yield of cereals in the event of abiotic stress. Abstract : Reduced photoinhibition via increased photoavoidance and photoprotection is an agronomic trait of interest that impacts both stress tolerance and yield. We have shown that null mutation of RGA1, encoding the canonical Gα subunit of the rice heterotrimeric G protein, improves photoavoidance and photoprotection and modulates the expression of related genes. This study highlights the potential of manipulation of G‐protein signalling for agronomic purposes.